1984
DOI: 10.1111/j.1476-5381.1984.tb10081.x
|View full text |Cite
|
Sign up to set email alerts
|

Contractions of rat uterine smooth muscle induced by acetylcholine and angiotensin II in Ca2+‐free medium

Abstract: 1The effects of acetylcholine (ACh,10-M) and angiotensin II (Ang II,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 34 publications
5
29
0
1
Order By: Relevance
“…5). A similar mechanism has been demonstrated in renal proximal tubule cells (12, 23, 32, 44, 49) and is consistent with the accepted contractile effect of angiotensin II on the myometrium, which involves AT 1 receptor activation and elevation of [Ca 2ϩ ] i (23,28,32).…”
Section: C563 Angiotensin II Activates Intracellular At1 Receptors Insupporting
confidence: 57%
“…5). A similar mechanism has been demonstrated in renal proximal tubule cells (12, 23, 32, 44, 49) and is consistent with the accepted contractile effect of angiotensin II on the myometrium, which involves AT 1 receptor activation and elevation of [Ca 2ϩ ] i (23,28,32).…”
Section: C563 Angiotensin II Activates Intracellular At1 Receptors Insupporting
confidence: 57%
“…Electrical activity was recorded with both conventional microelectrodes filled with 3 M KCI (resistance 40-50 MQ) and the double sucrose gap method (Mironneau, 1973 (Vassort & Rougier, 1972) and discussed in detail (Potreau & Raymond, 1983 (Lalanne et al, 1984). For longer applications of acetylcholine (2 min or more), the transient contraction was followed by a maintained response which lasted as long as the preparation was exposed to the agonist (Figure la (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…(ii) a Ca2+-influx through receptor-operated channels (Bolton & Kitamura, 1983); (iii) a release of Ca2+ ions from a limited intracellular Ca2+ store producing only one transient contraction (Casteels & Raeymaekers, 1979;Lalanne et al, 1984). However, it has also been reported that, during the same Ca2+-free perfusion, maintained contractions of myometrium can be repeatedly produced by different stimulant substances without diminution in size for 1 h or longer (Sakai et al, 1982;Lalanne et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NA was applied after 1.5 min in Ca2+-free solutions. Lalanne et al, 1984). Decreasing the temperature of the perfusing solution to 20C suppressed both electrical activity and calcium influx through voltagedependent channels.…”
Section: Diussionmentioning
confidence: 99%